SOME ASPECTS OF THE ESTIMATION OF STRUCTURAL-FUNCTIONAL CHANGES IN MEMBRANE OF ERYTHROCYTES AT THE CARDIOVASCULAR PATHOLOGY - E. E. Kuznetsova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents the estimation of structural-functional changes in erythrocytic membranes accompanied with the change of activity of different enzymes that determine normal functioning of erythrocytes. Change of lipid-protein and protein-protein interactions causes the reapportionment of charges on the surface of erythrocytes and. the decrease of total charge of cell and. leads to the increase of aggregation of erythrocytes and. the change of rheological properties of blood. In the end. it reflects on the effectiveness of oxygen transportation, transcapillary diffusion and perfusion of blood in microcirculation channel.